Dampak Implementasi Enterprise Resource Planning Terhadap Kualitas Informasi Keuangan, Manajemen Laba, Dan Return Of Equity - Abdul Roup; Edi Purwanto (Jurnal Ilmiah Akuntansi Kesatuan, 2022)
The purpose of this research is to provide evidence that the system of ERP can be relied on to give positive impact on the reporting system for enterprises. This research used the method of purposive sampling of the paired-t-test for the period of three years before the system of ERP was applied and three years after the system of ERP was applied. There are three findings resulted from this research. First is that by applying the system of ERP, the quality of financial information was increased significantly. The second finding is that by applying the system of ERP, the profit management quality was not decreased significantly. The third finding is that by applying the system of ERP, the company performance was increased significantly. Hopefully, this research will give beneficial input for the enterprises and the government who are about to adopt the system of ERP. Keywords: Enterprise Resource Planning, Quality of Financial Information, Profit Management, and Return of Equity.